QOCNTR: Improved NTRU Public Key based on a New Algebraic Structure - Eqbal Naji Hameed, Hassan Rashed Yassein (Mathematical Statistician and Engineering Applications, 2022)
This study proposes QOCNTR, a new multidimensional public key cryptosystem based on q-octonion algebra that improves security through a multidimensional approach. The proposed cryptosystem features two public keys, which distinguishes it from previous cryptosystems. This cryptosystem can encrypt thirty-two messages simultaneously from thirty-two different or independent sources, which is useful in certain applications. QOCNTR was shown to outperform NTRU, QTRU, and OTRU in terms of security. Finally, because the suggested system has a very high level of security, the results are considered extremely suitable.